Effect of prior outbreak work experience to future outbreak responses for nurses in Hong Kong: A cross-sectional study. Issue 5 (October 2022) - Chan, Chin Pok; Li, Kin Kit; Tang, Arthur; Wong, Samuel Yeung Shan; Wei, Wan In; Lee, Shui Shan; Kwok, Kin On
ABSTRACT: Background: During the early phase of the Coronavirus Disease 2019 (COVID-19) epidemic, health care workers had elevated levels of psychological distress. Historical exposure to disease outbreak may shape different pandemic responses among experienced health care workers. Aim: Considering the unique experience of the 2003 SARS outbreak in Hong Kong, this study examined the association between prior epidemic work experience and anxiety levels, and the mediating role of perceived severity of COVID-19 and SARS in nurses. Methods: In March 2020, a cross-sectional survey targeting practising nurses in Hong Kong was conducted during the early phase of the COVID-19 epidemic. The interrelationships among participants' work experience during the SARS outbreak, perceived severity of SARS and COVID-19, and anxiety level were elucidated using structural equation model (SEM). Findings: Of 1, 061 eligible nurses, a majority were female (90%) with a median age of 39 years (IQR = 32-49). A significant and negative indirect association was identified between SARS experience and anxiety levels (B=-0.04, p=0.04) in the SEM with a satisfactory fitness (CFI=0.95; RMSEA=0.06). SARS-experienced nurses perceived SARS to be less severe (B=-0.17, p=0.01), translated an equivalent perception to COVID-19 (B=1.29, p<0.001) and resulted in a lower level of anxiety (B=0.19, p<0.001). Conclusions: The less vigorous perception towards the severity of SARS and COVID-19 may explain SARS-experienced nurses' less initial epidemic-induced anxiety. The possible role of outbreak-experienced nurses in supporting outbreak-inexperienced nurses, both emotionally and technically, should be considered when an epidemic commences. Interventions aiming to facilitate the understanding of emerging virus should also be in place.